2000
DOI: 10.1006/viro.2000.0244
|View full text |Cite
|
Sign up to set email alerts
|

Coding Changes in the Poliovirus Protease 2A Compensate for 5′NCR Domain V Disruptions in a Cell-Specific Manner

Abstract: Polioviruses are single-stranded RNA viruses with an unusually long noncoding region (NCR) at the 5' end predicted to have an elaborate secondary structure made up of six domains. Mutations in domain V of the poliovirus 5'NCR that disrupt secondary structure are responsible for attenuation of the virus and a temperature-sensitive (ts) phenotype in vitro. In addition to direct back mutation or compensatory second site mutation in the 5'NCR as previously documented, the ts phenotype was found to be compensated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…It had been suggested initially that the 2A protease may directly interact with the IRES element (27), but the internal location of some of the residues modified in the revertant viruses appears to make this unlikely. It has now been suggested that these mutations may disrupt a protein-protein interaction (32). Indeed, on the basis of our results, these substitutions, which served to overcome the deficit in translational efficiency imposed by the IRES mutation, may function by modifying the interaction of the PV 2A protease with some cellular component involved in the activation of IRES activity.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It had been suggested initially that the 2A protease may directly interact with the IRES element (27), but the internal location of some of the residues modified in the revertant viruses appears to make this unlikely. It has now been suggested that these mutations may disrupt a protein-protein interaction (32). Indeed, on the basis of our results, these substitutions, which served to overcome the deficit in translational efficiency imposed by the IRES mutation, may function by modifying the interaction of the PV 2A protease with some cellular component involved in the activation of IRES activity.…”
Section: Discussionmentioning
confidence: 52%
“…Two out of 10 such mutants analyzed had substitutions in residues adjacent to the catalytic triad, and the other substitutions were predicted to occur in two main clusters on the protease surface. Recently additional mutations in 2A that have this effect have been identified (32). It had been suggested initially that the 2A protease may directly interact with the IRES element (27), but the internal location of some of the residues modified in the revertant viruses appears to make this unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one of the mutations which gave rise to reversions in 2A was the first nucleotide of the bulge under study here. Interestingly, the compensatory effect of 2A changes was found to be cell specific (33).…”
Section: Discussionmentioning
confidence: 96%
“…All these modifications observed in the 5 0 NTR and in the 2A gene, allow us to conclude that the virus has adapted to the cell, as it has been observed for the poliovirus [37]. In addition, a study of the impact of the modified 2A protein on the Dev cell line is necessary to complete our knowledge about the role of the mutated 2A pro in the viral persistence.…”
Section: Discussionmentioning
confidence: 85%